2023
DOI: 10.3389/fmicb.2023.1192449
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of probiotic strain Lactiplantibacillus plantarum MYSN7 against Trichophyton tonsurans

Abstract: The primary objective of this study was to assess the probiotic attributes and antifungal activity of lactic acid bacteria (LAB) against the fungus, Trichophyton tonsurans. Among the 20 isolates screened for their antifungal attributes, isolate MYSN7 showed strong antifungal activity and was selected for further analysis. The isolate MYSN7 exhibited potential probiotic characteristics, having 75 and 70% survival percentages in pH3 and pH2, respectively, 68.73% tolerance to bile, a moderate cell surface hydroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Hydrophobicity is another limiting factor in probiotic potential as it may influence the ability of a strain to adhere and grow on different surfaces and it can offer a competitive advantage in the adhesion of LAB [17,30,31]. Therefore, a higher cell surface hydrophobicity can be regarded as a useful feature for adherence to human intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrophobicity is another limiting factor in probiotic potential as it may influence the ability of a strain to adhere and grow on different surfaces and it can offer a competitive advantage in the adhesion of LAB [17,30,31]. Therefore, a higher cell surface hydrophobicity can be regarded as a useful feature for adherence to human intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of fermented cranberry juice and antibiotics has an antibacterial synergistic effect. Metabolites of lactic acid bacteria and phenolic compounds in cranberry juice help to better inhibit the growth of pathogenic bacteria ( Loanna et al, 2019 , Vanitha et al, 2023 , Divyashree et al, 2023 ) studied the inhibitory activity of Candida Lactobacillus plantarum MYSAS1 and Enterococcus faecium MYSAS4 isolated from fermented black cherry fruits against Salmonella enterica . The results showed that these two kinds of lactobacillus had inhibitory effects on Escherichia coli , Klebsiella pneumoniae , Pseudomonas aeruginosa , Staphylococcus aureus and Salmonella paratyphi , especially the inhibition rate of Lactobacillus plantarum could reach more than 80 %.…”
Section: Functional Activities Of Fermented Fruit and Vegetable Juicementioning
confidence: 99%